Investigating changes in scientists’ ethical decision making and course design - Garcia, Tyler (Kansas State University, 2024)
One way to bring about change in higher education is to introduce professional development programs for higher education, however these programs have been found to be ineffective at promoting positive change for individuals and departments. To address the need for better programs, I worked on two projects: one project attempts to identify a way to improve Responsible Conduct of Research training and the other project is an assessment designed to be distributed in a Thermal and Statistical Physics course that supports instructors on improving their curriculum. Many scientists view science as value-free, despite the fact that both epistemic and non-epistemic values structure scientific inquiry. Current Responsible Conduct of Research training usually focuses on transmitting knowledge about high-level ethical concepts or rules and is widely regarded as ineffective. We argue that Responsible Conduct of Research training will be more effective at improving ethical decision making if it focuses on connecting values to science. Due to the investigation of research ethics education in physics being relatively new, we pull from philosophy and psychology to define ethical decision making using the Four Component Model. This model states that in order to make an ethical decision someone must consider four components: moral sensitivity, moral reasoning, moral motivation, and moral implementation. For this study we formed a moderated fellowship of fourteen science faculty from different disciplines who met for ten sessions over the course of a year, where they discussed the values embedded in different scientific norms. We then conducted interviews before and after the year-long fellowship that involved guided reflection of scenarios where there was some kind of ethical misconduct where the scientific practice required value judgements (e.g using unpublished data). From this data we looked at how the fellowship affected the scientists’ ability to recognize ethical dimensions in their work. We found that this fellowship improves moral sensitivity, but their moral reasoning does not change. We then identified a more precise approach to looking at scientists’ moral reasoning. This work can inform future ethical training to align better with what scientists value and introduce useful concepts from philosophy and psychology to education research in physics. There are calls to create assessments that focus on gathering evidence that shows both knowledge of the desired subject and transferable skills between disciplines while providing useful feedback to instructors. To answer this call, we created a thermal and statistical physics assessment that provides evidence of student knowledge and skills in a thermal or statistical physics course that also provides actionable feedback to instructors. To create tasks, we use a knowledge-in-use framework that focuses on identifying the evidence we need to see in student answers to claim students are able to do physics, not just know physics. These “evidence statements" are the observable features students generate that show they have knowledge to complete a claim. We need to determine a way to validate the tasks based on the focus towards obtaining evidence of student abilities when solving tasks. Current literature focuses on bringing in experts to validate whether the tasks are at the right level for the students. We are looking to expand on literature in Physics Education Research (PER) by articulating a way to validate tasks that use evidence-centered design through looking at students’ evidence statements. To validate the assessment, we identified new components to gather evidence towards validation. Using these new components we introduced a new methodology to validate assessments that focus on delivering feedback through evidence. We have conducted and analyzed student think-aloud interviews answering the tasks in a free-response format or in a Coupled Multiple-Response format. We also conducted faculty interviews to see if the tasks are relevant to their courses. Through these interviews we developed a new methodology of contributing to the validation of assessments that focus on faculty feedback. This dissertation introduces new methodologies for future researchers to improve on Responsible Conduct of Research trainings and assessment designed for supporting instructor curriculum. Through these new methodologies scientists can address the calls for better professional development programs in higher education.
Keywords: RCR; Assessment; Validation